2015
DOI: 10.1080/14786419.2015.1079910
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and phytotoxic activity of essential oil from root of Senecio amplexicaulis Kunth. (Asteraceae) growing wild in high altitude-Himalayan region

Abstract: This work was aimed to evaluate the essential oil from root of medicinally important plant Senecio amplexicaulis for chemical composition, antifungal and phytotoxic activity. The chemical composition analysed by GC/GC-MS showed the presence of monoterpene hydrocarbons in high percentage with marker compounds as α-phellandrene (48.57%), o-cymene (16.80%) and β-ocimene (7.61%). The essential oil exhibited significant antifungal activity against five phytopathogenic fungi, Sclerotium rolfsii, Macrophomina phaseol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The EO extracted from Majorana hortensis showed the presence of β ‐phellandrene as major compounds, where this EO exhibited significant allelopathic activity against Raphanus sativus , Lactuca sativa , and Lepidium sativum [49] . While α ‐phellandrene and o ‐cymene, the major constituents of Senecio amplexicaulis EO, attained considerable allelopathic effect on Phalaris minor and Triticum aestivum [50] . The p‐ cymene has been reported as a major compound with the allelopathic activity of the EOs of several plants such as Artemisia scoparia , [51] Thymus daenensis , [52] Origanum acutidens , [53] and Eucalyptus grandis [54] .…”
Section: Resultsmentioning
confidence: 99%
“…The EO extracted from Majorana hortensis showed the presence of β ‐phellandrene as major compounds, where this EO exhibited significant allelopathic activity against Raphanus sativus , Lactuca sativa , and Lepidium sativum [49] . While α ‐phellandrene and o ‐cymene, the major constituents of Senecio amplexicaulis EO, attained considerable allelopathic effect on Phalaris minor and Triticum aestivum [50] . The p‐ cymene has been reported as a major compound with the allelopathic activity of the EOs of several plants such as Artemisia scoparia , [51] Thymus daenensis , [52] Origanum acutidens , [53] and Eucalyptus grandis [54] .…”
Section: Resultsmentioning
confidence: 99%
“…Monoterpenes are also involved in plant–fungus interactions. The essential oils α‐phellandrene, o‐cymene and β‐ocimene from Senecio amplexicaulis exhibited antifungal activity against phytopathogenic fungi, and phytotoxic activity against Phalaris minor and Triticum aestivum …”
Section: Chemistrymentioning
confidence: 99%
“…The essential oils -phellandrene, o-cymene and -ocimene from Senecio amplexicaulis exhibited antifungal activity against wileyonlinelibrary.com/journal/ps phytopathogenic fungi, and phytotoxic activity against Phalaris minor and Triticum aestivum. 87 Menthol has high antibacterial activity against Staphylococus aureus, Escherichia coli and Bacilus cereus. In the case of Mentha × piperita L., which produces this monoterpene, improved bactericidal activity over the whole growing season of the plant is associated with higher production of this monoterpene.…”
Section: Monoterpenesmentioning
confidence: 99%
“…Singh et al [ 84 ] evaluated the antifungal effects of the EOs extracted from Senecio amplexicaulis , which had alpha-phellandrene as its main compound (48.6%). The experiment showed that the EO had strong antifungal activity in a concentration that ranged between 157.0 to 199.3 µg/mL against different fungal species ( Macrophomina phaseolina , Rhizoctonia solani , Sclerotium rolfsii , Fusarium oxysporum and Pythium debaryanum ).…”
Section: Resultsmentioning
confidence: 99%